2009
DOI: 10.1144/sp325.12
|View full text |Cite
|
Sign up to set email alerts
|

Plant assemblages from SW Gondwana: further evidence for high-latitude vegetation in the Devonian of Argentina

Abstract: Plant assemblages are described from the Talacasto and Punta Negra Formations, San Juan Province, the Argentine Precordillera. A detailed facies study involving trace fossil assemblages indicates that the plants were buried in shallow low-to high-energy marine environments, but not in turbidites as previously postulated. Apart from a single specimen resembling Cooksonia from the Lochkovian Talacasto Formation, the abundant compression fossils consist of short lengths of smooth axes, occasional defoliated lycop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 43 publications
2
24
0
10
Order By: Relevance
“…Limachi et al, 1996;di Pasquo et al, 2009;Edwards et al, 2009;Matsumura et al, , 2014 is poorly known. There appear to be many hiatuses in between the plant assemblages documented up to now (Fig.…”
Section: Biostratigraphic Discussion and Correlationmentioning
confidence: 99%
“…Limachi et al, 1996;di Pasquo et al, 2009;Edwards et al, 2009;Matsumura et al, , 2014 is poorly known. There appear to be many hiatuses in between the plant assemblages documented up to now (Fig.…”
Section: Biostratigraphic Discussion and Correlationmentioning
confidence: 99%
“…More recently, however, it has been interpreted as a shallow marine inner shelf to locally continental environment by Edwards et al (2009), as suggested by the taphonomy of plant remains.…”
Section: Geological Setting and Provenance Of The Materialsmentioning
confidence: 99%
“…Its leaf bases, however, tend to be more hexagonal than those of the Moroccan specimen. The second specimen from Argentina, which is also 9 mm wide, was referred to as specimen LPPB 13267 by Edwards et al (2009) and illustrated in their Fig. 7c.…”
Section: Lycophytes -Lycopsidamentioning
confidence: 99%
“…The leaf bases of this specimen do not show any obvious notch, a feature possibly specific to the Moroccan stems. Because leaf laminae were not preserved, Edwards et al (2009) did not assign their fossil to any taxon but simply inferred that it belonged to an herbaceous lycophyte with persistent leaf bases. The same approach is taken in this paper for the undetermined lycopsid from Dechra Aït Abdallah.…”
Section: Lycophytes -Lycopsidamentioning
confidence: 99%